How Does Tropical Cyclone‐Induced Remote Moisture Transport Affect Precipitation Over East Asia - Shiqi Xiao; Aoqi Zhang; Yilun Chen; Shumin Chen; Weibiao Li (Geophysical Research Letters)
Abstract Analyzing tropical cyclone‐induced remote moisture transport clusters (TRCs) and their effects on precipitation is crucial for understanding precipitation formation and enhancing forecast precision. Prior research, primarily case‐based, did not fully grasp the nature of TRCs. Utilizing an objective TRC identification method, we categorized 65 TRC tracks in East Asia into five types and examined their traits and precipitation links. The findings indicate that the moisture transport height of TRCs varies due to multiple factors, with higher transport linked to the warm conveyor belt and lower transport attributed to Taiwan’s mountain range influencing low‐level moisture. The precipitation peak altitudes of TRCs at higher latitudes are greater, and their precipitation intensity is positively correlated with terrain type, especially coastlines. This study underscores the diversity in TRC characteristics and related precipitation, suggesting that future research should consider the directionality of TRC tracks.